On the solution structure of kraft lignin in ethylene glycol and its implication for nanoparticle preparation. Issue 1 (6th September 2018) - Yang, Mingkun; Zhao, Wenwen; Singh, Seema; Simmons, Blake; Cheng, Gang
Abstract : Ethylene glycol (EG) starts to attract attention as a robust solvent for lignin processing. Abstract : Ethylene glycol (EG) starts to attract attention as a robust solvent for lignin processing. However its solution structure has not been revealed. In this effort, small angle neutron scattering (SANS) and dynamic light scattering are used to understand the dissolution of kraft lignin in EG and the impact of the resultant solution structure on nanoparticle preparation. Lignin solutions with different concentrations (0.6 to 13.0 wt%) were explored by SANS, allowing evaluation of the solvent quality, the conformation of lignin subunits and their aggregation in EG. Molecular interactions between EG and lignin were discussed and compared to those between DMSO and lignin. The process of nanoparticle preparation from EG solutions upon addition of anti-solvents was also discussed.